Abnormal regional brain activity associated with relapse in early abstinent methamphetamine-dependent individuals - Ming Ma; Tiancheng Yu; Zhi Qin; Peng Zhao; Mudi Zhao; Jianye Guo; Ningqing Huang; Mengqian Liu; Kaixi Zhang; Qian Cai; Jianhuai Chen; Guoxiang Wang (Scientific Reports)
Abstract Methamphetamine (MA) can cause functional abnormalities in the brain. However, the correlations between the abnormal brain activity and relapse in abstinent MA-dependent individuals (MADIs) were still unclear. This study aimed to explore the changes of regional brain activation associated with relapse in early abstinent MADIs, which could provide potential neuroimaging markers for predicting the relapse susceptibility. Twenty-seven individuals who relapsed to MA within 1 year after abstaining from MA, as well as 28 healthy controls (HCs), were enrolled in this study. Resting-state functional magnetic resonance imaging (rs-fMRI) collected from all HCs, and MADIs when they were abstinent from MA (Stage I) and relapsed to MA (Stage II). The measures for evaluating regional brain activity including regional homogeneity (ReHo) and fractional amplitude of low-frequency fluctuation (fALFF) were calculated for all participants. ReHo and fALFF values were compared between MADIs at Stage I, Stage II and HCs. Finally, relationships between altered brain regions and duration of MA use, duration of relapse were evaluated by Pearson correlation analysis. Compared with HCs, MADIs at Stage I demonstrated decreased brain activity in three cortical regions and increased brain activity in several subcortical regions, especially bilateral putamen. In addition, MADIs at Stage II exhibited a wider range of brain regions with abnormal activity, which presented as decreased activity mainly in the middle cingulate gyrus, parietal and occipital regions, and increased activity mostly in the subcortical regions (striatum, thalamus and hippocampal structure) and several prefrontal regions. Moreover, MADIs at Stage II showed decreased activity in the parietal regions and increased brain activity in the prefrontal and subcortical regions, especially bilateral caudate nucleus. The fALFF values of left and right caudate nucleus were negatively associated with duration of relapse. There were still abnormal activities in the brain of MADIs even when they were abstinent from MA. Increased activity in the bilateral putamen might be associated with early relapse in abstinent MADIs. Relapse to MA use could cause more wider range of abnormal brain activity, especially increased activity in the striatum, which might lead to more higher relapse rate of MA use.